2023
DOI: 10.21203/rs.3.rs-2597370/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

“Everyone needs a Deb”: what Australian Indigenous women say about breast cancer screening and treatment services

Abstract: Background Breast cancer continues to be the second most diagnosed cancer and the most diagnosed cancer for women in Australia. While mortality rates overall have declined in recent years, Indigenous women continue to be diagnosed at more marginal rates (0.9 times) and are more likely to die (1.2 times). This is also the case for Indigenous women in high income countries globally. The literature provides a myriad of reasons for this; however, the voices of Indigenous women are largely absent. This study sets … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…[12] Several studies found that ethnic minority immigrant women experience inadequate and inequitable access to health care and community services. [9][10][11][12] The unique cultural beliefs of ethnic minorities and people who immigrate to Canada influence their health and illness experiences and lead to lower breast cancer screening rates. [13][14][15] Owing to communication barriers, [16] lack of knowledge, [17] and low health literacy, [14,18] immigrant women find it difficult to navigate health care services and to establish relationships with health care providers.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…[12] Several studies found that ethnic minority immigrant women experience inadequate and inequitable access to health care and community services. [9][10][11][12] The unique cultural beliefs of ethnic minorities and people who immigrate to Canada influence their health and illness experiences and lead to lower breast cancer screening rates. [13][14][15] Owing to communication barriers, [16] lack of knowledge, [17] and low health literacy, [14,18] immigrant women find it difficult to navigate health care services and to establish relationships with health care providers.…”
Section: Introductionmentioning
confidence: 99%
“…[11] In another research study, understanding issues related to access, awareness, and the role of health care affected the engagement of Indigenous women in accessing breast cancer diagnosis and treatment services. [12] Several studies found that ethnic minority immigrant women experience inadequate and inequitable access to health care and community services. [9][10][11][12] The unique cultural beliefs of ethnic minorities and people who immigrate to Canada influence their health and illness experiences and lead to lower breast cancer screening rates.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations